Teaching language and literacy : policies and procedures for vernacular situations - Craig, Dennis R. (Education and Development Services Inc GeorgetownGY, 1999)
Explores the problem of students finding difficulty in acquiring standard Englosh and literacy in English and provides guidelines for its solution.